تطبيق محاسبة الموارد البشرية في المؤسسات الاقتصادية الجزائرية (الدوافع وإشكالية القياس) -دراسة ميدانية بالشركة الوطنية للكهرباء والغاز بورقلة - خامرة, الطاهر (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة لإبراز دوافع وصعوبات تطبيق محاسبة الموارد البشرية في المؤسسة الاقتصادية الجزائرية، إلى جانب الطرق المفضلة في القياس ميدانيا. تم تطبيق هذه الدراسة ميدانيا بمصالح قسم المالية والمحاسبة لشركة سونلغاز بورقلة، وذلك باستخدام المنهج الوصفي لتقصي أراء المهنيين في المحاسبة من خلال أداة الاستبيان. توصلت الدراسة أن هناك عدة دوافع لتطبيق محاسبة الموارد البشرية في الشركة، في حين لم يتم قبول أي طريقة من طرق قياس المورد البشري، وتبقى طريقة التكلفة التاريخية هي الأقرب للتطبيق، كما تم الاتفاق على مجموعة من صعوبات تطبيق محاسبة الموارد البشرية، وفي العموم هذه النتائج بنفس الدرجة لجميع مصالح قسم المالية والمحاسبة بشركة سونلغاز. The study aims to highlight the motives and difficulties of applying HRA in the Algerian economic entreprise and the preferred methods of its measurement. This field study was held in the finance and Accounting department in Sonelgaz – Ouargla, using the descriptive approach to investigate the opinions of the accountants of Sonelgazthrough a questionnaire. The study found that there are several motives for applying human resources accounting in the company, while no method of measuring human resources has been accepted, and the historical cost method remains the closest to apply.It was also agreed on a set of difficulties in applying HRA. In general, these results are the same for all the sections of the Finance and accounting department of Sonelgaz
The application of human resources accounting in the Algerian economic entreprises (motives and the problem of measurement): A field study at SONELGAZ – Ouargla
مقال
Keywords: دوافع تطبيق محاسبة موارد بشرية ; طرق قياس مورد بشري ; صعوبات تطبيق محاسبة موارد بشرية ; سونلغاز